PENERAPAN MATERIAL RAMAH LINGKUNGAN PADA PERANCANGAN ASRAMA MAHASISWA UNIVERSITAS TARUMANAGARA DI JAKARTA BARAT - Thejaya, Hansen; Husin, Denny (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2025)
The growth in the number of students at Tarumanagara University in West Jakarta increases the need for adequate and sustainable housing. Urban environmental issues such as the energy crisis, the heat island effect, and limited green space demand responsive and sustainable architectural solutions. This study aims to design a Untar student dormitory with a green architecture approach, especially through the selection of building forms and materials that support energy efficiency, thermal comfort, and sustainability. The design method is carried out through literature studies, site and climate analysis, and design synthesis based on passive design principles. The design results show that building forms based on solar orientation and cross ventilation, as well as the selection of local materials such as perforated bricks and bamboo, are able to create a healthy, energy-efficient, and urban biodiversity-supporting residential environment. This design can be a model for sustainable housing in a dense campus environment in a big city.  In addition to considering environmental aspects, the design also integrates the social and psychological needs of students by providing communal spaces that encourage interaction, collaboration, and a sense of togetherness. The arrangement of building masses and open spaces is chosen to maximize natural lighting, air circulation, and visual connection with surrounding greenery. This approach not only improves occupant comfort but also reduces reliance on mechanical systems such as air conditioning and artificial lighting. Therefore, this dormitory design not only addresses the need for student housing but also plays an active role in creating a more environmentally friendly and long-term sustainable campus environment. Keywords: Biodiversity; Environmentally Friendly Materials; Green Architecture Abstrak Pertumbuhan jumlah mahasiswa Universitas Tarumanagara di Jakarta Barat meningkatkan kebutuhan akan hunian yang memadai dan berkelanjutan. Isu lingkungan perkotaan seperti krisis energi, efek pulau panas, dan keterbatasan lahan hijau menuntut solusi arsitektur yang responsif dan berkelanjutan. Studi ini bertujuan merancang asrama mahasiswa Untar dengan pendekatan arsitektur hijau, khususnya melalui pemilihan bentuk dan material bangunan yang mendukung efisiensi energi, kenyamanan termal, dan keberlanjutan. Metode perancangan dilakukan melalui studi literatur, analisis tapak dan iklim, serta sintesis desain berbasis prinsip desain pasif. Hasil perancangan menunjukkan bahwa bentuk bangunan berbasis orientasi matahari dan ventilasi silang, serta pemilihan material lokal seperti bata berlubang dan bambu, mampu menciptakan lingkungan hunian yang sehat, hemat energi, dan mendukung biodiversitas urban. Desain ini dapat menjadi model hunian berkelanjutan di lingkungan kampus padat kota besar. Selain mempertimbangkan aspek lingkungan, rancangan juga mengintegrasikan kebutuhan sosial dan psikologis mahasiswa melalui penyediaan ruang-ruang komunal yang mendorong interaksi, kolaborasi, dan rasa kebersamaan. Strategi penataan massa bangunan dan ruang terbuka dipilih untuk memaksimalkan pencahayaan alami, sirkulasi udara, serta koneksi visual dengan elemen hijau di sekitarnya. Pendekatan ini tidak hanya meningkatkan kenyamanan penghuni, tetapi juga mengurangi ketergantungan pada sistem mekanis seperti pendingin udara dan pencahayaan buatan. Dengan demikian, rancangan asrama ini tidak hanya menjawab kebutuhan tempat tinggal, tetapi juga berperan aktif dalam menciptakan lingkungan kampus yang lebih ramah lingkungan dan berorientasi pada keberlanjutan jangka panjang.